1984
DOI: 10.1111/j.1939-0025.1984.tb01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year follow-up of pupils in a special class for the mentally retarded: A study of a complete school community.

Abstract: Long-term individual follow-up of a class of 18 mildly mentally retarded pupils and of a larger group of their contemporaries--at three and at 20 years after primary school--raises questions about theories and assumptions that serve as a basis for educational and health policies affecting such students. The particular importance of interdisciplinary education and cooperation among professionals serving this population is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Carter and Jancer (1984) found that suicidal behavior was the cause of death in only one case in a series of 204 sudden deaths over a 50-year period. Bloch (1984) conducted a 3-and 20-year follow-up report of 18 persons with mild mental retardation who had been in special education. He found that one suicide had occurred in this group.…”
Section: Introductionmentioning
confidence: 99%
“…Carter and Jancer (1984) found that suicidal behavior was the cause of death in only one case in a series of 204 sudden deaths over a 50-year period. Bloch (1984) conducted a 3-and 20-year follow-up report of 18 persons with mild mental retardation who had been in special education. He found that one suicide had occurred in this group.…”
Section: Introductionmentioning
confidence: 99%